PENINGKATAN LITERASI DIGITAL KELOMPOK IBU RUMAH DI KAMPUNG NITIPRAYAN YOGYAKARTA - Ningrum, Dyaloka Puspita; Syakdiah, Syakdiah (Jurnal Abdi Insani, 2025)
It is inevitable that industry 4.0 has become a new phenomenon that makes human life very dependent on digital technology. Online media products are also increasingly mushrooming in their use which can positively help public activities in various sectors of life. Including the presence of social media which is currently very multifunctional, and can even provide quite promising financial benefits. This Community Service Activity aims to educate groups of housewives in Nitiprayan Village, Yogyakarta to be more productive and have a commitment to taking advantage of opportunities in the digital era. The method of implementing the activity is carried out in stages and face to face, namely: oral presentations, interactive discussions, simulations and special evaluations by the facilitator team. This activity was attended by 25 participants, which was held at the Nitibudoyo Studio, Nitiprayan Village, Bantul Regency, Yogyakarta. The superiority of local culture inherent in the activity location becomes capital that can be elaborated in the media activities of the partner group. Although the beneficiary group must still choose the most potential digital platform with their respective expertise. Simple ideas can in principle be created from habits that are often done at home. So that this activity is expected to answer the gap in access to the use of modern communication technology, especially those that are suspected to occur a lot among women. That way, issues related to the generation gap, especially in the use of gadgets and even adaptation to the latest trends which are inevitable, will be easier to overcome, even with the most enjoyable efforts. Activity participants gain new experiences to be able to directly practice creating content that can then be disseminated through their social media.